2019
DOI: 10.1038/s41598-019-41273-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spheroidal Age on Sorafenib Diffusivity and Toxicity in a 3D HepG2 Spheroid Model

Abstract: The enhanced predictive power of 3D multi-cellular spheroids in comparison to conventional monolayer cultures makes them a promising drug screening tool. However, clinical translation for pharmacology and toxicology is lagging its technological progression. Even though spheroids show a biological complexity resembling native tissue, standardization and validation of drug screening protocols are influenced by continuously changing physiological parameters during spheroid formation. Such cellular heterogeneities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 47 publications
4
56
0
Order By: Relevance
“…Analysis of the data obtained by TEM, SEM and light microscopy, clearly indicates that bile capillaries never come to the surface; they are "hidden" inside the spheroids. Correct identification of bile capillaries in HepG2 spheroids by TEM was reported in [ 14 ], and some published TEM studies of HEpG2 spheroids demonstrated pseudosinusoids instead bile capillaries [ 48 , 50 ].…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Analysis of the data obtained by TEM, SEM and light microscopy, clearly indicates that bile capillaries never come to the surface; they are "hidden" inside the spheroids. Correct identification of bile capillaries in HepG2 spheroids by TEM was reported in [ 14 ], and some published TEM studies of HEpG2 spheroids demonstrated pseudosinusoids instead bile capillaries [ 48 , 50 ].…”
Section: Resultsmentioning
confidence: 90%
“…Previously published studies showed changes in the shape and compactization of HepG2 spheroids during their development; early, middle and late stages of spheroid growth were identified, the duration of which varied in different works and mainly depended on the dose of cell seeding. Common recommendation was to work with HepG2 spheroids at middle stage (beginning from days 4–5 after cell seeding) which is characterized by active function of spheroid cells and absence of cell destruction [ 10 , 14 , 45 ]. Amount of published studies using HEK293 spheroids is incomparably less than studies with HepG2 spheroids; however, authors noted a very fast compactization of HEK293 cells on a non-adhesive surface and regular spherical shape of the spheroids [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations